Simulation and psychological trainings as methods of preventing emotional burnout in doctors - Лефтеров, Василь Олександрович; Лефтеров, В. О.; Лефтеров, Василий Александрович; Lefterov, Vasyl O.; Тімченко, Олександр Володимирович; Тімченко, О. В.; Тимченко, Александр Владимирович; Timchenko, Oleksandr V.; Цільмак, Олена Миколаївна; Цільмак, О. М.; Цильмак, Елена Николаевна; Tsilmak, Olena M.; et al. (Scientific society of anatomists, histologists, embryologists and topographoanatomists of Ukraine, 2020)
The article analyzed the problem of emotional burnout in doctors, as well as the features of using and implementing medical simulation tools in the training process of medical specialists. The results of an empirical study of the simulation and psychological training effects on the psychological correction and the burnout syndrome prevention in doctors were presented. It was found that after these trainings doctors have reduced rates of emotional exhaustion, depersonalization, and improved well-being and mood. It was recommended to perform diverse psychological trainings and other psychological support and consulting procedures in the simulation training system.

У статті здійснюється аналіз проблеми емоційного вигорання лікарів, а також особливостей використання і впровадження засобів медичної симуляції в процес підготовки медичних фахівців. Наводяться результати емпіричного дослідження впливу симуляційних та психологічних тренінгів на психокорекцію і профілактику синдрому емоційного вигорання лікарів. Встановлено, що після зазначених тренінгів у лікарів значимо знижуються показники емоційного виснаження, деперсоналізації, поліпшується самопочуття і настрій. Рекомендовано проведення в системі симуляційного навчання різнопланових психологічних тренінгів та інших процедур психологічного супроводу та консалтингу.

В статье проводится анализ проблемы эмоционального выгорания врачей, а также особенностей использования и внедрения средств медицинской симуляции в процесс подготовки медицинских специалистов. Приводятся результаты эмпирического исследования влияния симуляционных и психологических тренингов на психокоррекции и профилактики синдрома эмоционального выгорания врачей. Установлено, что после указанных тренингов у врачей значимо снижаются показатели эмоционального истощения, деперсонализации, улучшается самочувствие и настроение. Рекомендуется проведение в системе симуляционных обучения разноплановых психологических тренингов и других процедур психологического сопровождения и консалтинга.
Lefterov V. O. Simulation and psychological trainings as methods of preventing emotional burnout in doctors / V. O. Lefterov, О. V. Timchenko, О. M. Tsilmak, I. I. Ignatieva // «World of Medicine and Biology». – № 2 (72). – Scientific society of anatomists, histologists, embryologists and topographoanatomists of Ukraine, 2020. – P. 85-89.
Keywords: medical simulation tools; simulation training; psychological training; burnout syndrome; psychological correction and prevention; засоби медичної симуляції; симуляційний тренінг; психологічний тренінг; синдром емоційного вигорання; психокорекція та профілактика; средства медицинской симуляции; симуляционный тренинг; психологический тренинг; синдром эмоционального выгорания; психокоррекция и профилактика; Research Subject Categories::MEDICINE